STRATEGI PENGAMBILAN KEPUTUSAN KEPALA SEKOLAH DALAM MENINGKATKAN EFEKTIFITAS MANAJEMEN MAN I BANYUWANGI - Afrida Nur Laili (CV Putra Publisher, 2022)
This study aims to find out how the decision-making strategy of the head of Madrasah in improving the effectiveness of management at MAN I Banyuwangi and to find out how the participation of teachers in decision-making by the head of Madrasah to improve Management Effectiveness in MAN I Banyuwangi. The method used in this study uses a qualitative method. The main data sources in this study are human and non-human, the human data sources are school principals and teachers or other staff and the data is formed in interview transcripts and field notes, while non-human data is documentation containing matters relating to related to educational management. The data analysis used in this research is interactive analysis, namely reducing data, presenting data and drawing conclusions. The results of this research indicate that an important strategy in decision making is to involve stakeholders in the MAN I Banyuwangi environment. The involvement of teachers and various parties in decision making will affect the implementation of increasing the effectiveness of school management as happened in MAN 1 Banyuwangi.